Analyses of the Spatial Pattern of Drought Risk in Tigray Region, Northern Ethiopia - A.S. Tefera; J.O. Ayoade; N.J. Bello (Journal of Applied Sciences and Environmental Management)
Drought risk index uses the meteorological drought hazard index and the socioeconomic drought vulnerability aspects to assess the level of drought risk in an area. This study examined the extent and spatial pattern of drought risk in, Tigray region, one of the recurrently drought-affected areas in Ethiopia. Monthly Gridded Climatic Research Unit (CRU) Time-series (TS) data version 4.01 data on twelve selected stations, was used to calculate the Standard Precipitation and Evapotranspiration Index (SPEI). Additionally, socioeconomic data collected from various sources were also used to assess drought vulnerability. Drought risk levels of each district were, then calculated based on the drought hazard and drought vulnerability indices. The results indicated that about 44.1% of districts were categorized under high to very high drought risk levels. However, the test of variation, using one-way ANOVA, has shown no significant variation in drought risk between districts at p < 0.05. The results of spatial autocorrelation test also indicated the presence of clustered pattern of drought risk. The study has also revealed high and very high drought risk levels largely clustered in the western, eastern and southern zones of the study area. Overall, the study has demonstrated the importance of integrating socioeconomic and climate data for comprehensive drought risk characterization, which can be used as an input for drought management planning.